Hyaluronan as "Agent Smith" in cancer extracellular matrix pathobiology: Regulatory roles in immune response, cancer progression and targeting. Issue 10 (8th March 2022) - Kokoretsis, Dimitris; Maniaki, Evangelia‐Konstantina; Kyriakopoulou, Konstantina; Koutsakis, Christos; Piperigkou, Zoi; Karamanos, Nikos K.
Abstract: Extracellular matrix (ECM) critically regulates cancer cell behavior by governing cell signaling and properties. Hyaluronan (HA) acts as a structural and functional ECM component that mediates critical properties of cancer cells in a molecular size‐dependent manner. HA fragments secreted by cancer‐associated fibroblasts (CAFs) reveal the correlation of HA to CAF‐mediated matrix remodeling, a key step for the initiation of metastasis. The main goal of this article is to highlight the vital functions of HA in cancer cell initiation and progression as well as HA‐mediated paracrine interactions among cancer and stromal cells. Furthermore, the HA implication in mediating immune responses to cancer progression is also discussed. Novel data on the role of HA in the formation of pre‐metastatic niche may contribute towards the improvement of current theranostic approaches that benefit cancer management.